1934
DOI: 10.1029/tr015i002p00454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of channel‐contraction works upon regimen of movable bed‐streams

Abstract: When water flows in an open channel having an erosible bed a condition of equilibrium is approached in which the water ceases to cause further erosion of its bed, although sedimentary material is continuously transported by the stream. Various control‐measures required to improve the conditions of a river‐system for use in navigation, irrigation, and power‐development set up a new regimen or condition of equilibrium of the system. Thus, for example, channel‐contraction works (structures used for narrowing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1964
1964
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…These amounts of moving sand are so small that they can usually be disregarded in studies of scour and fill. SOME PREVIOUS STATEMENTS OR USES OF THE PRINCIPLES Straub (1934) computed scour for constant flow at a laterally contracted cross section from his form of the Du Boys equation and from the principle of continuity of the bedload discharge. He concluded that observed amounts of scour at narrower-than-average cross sections of a stream probably were not representative of long reaches of a river.…”
Section: D7mentioning
confidence: 99%
“…These amounts of moving sand are so small that they can usually be disregarded in studies of scour and fill. SOME PREVIOUS STATEMENTS OR USES OF THE PRINCIPLES Straub (1934) computed scour for constant flow at a laterally contracted cross section from his form of the Du Boys equation and from the principle of continuity of the bedload discharge. He concluded that observed amounts of scour at narrower-than-average cross sections of a stream probably were not representative of long reaches of a river.…”
Section: D7mentioning
confidence: 99%
“…These equations involve one soil parameter: the mean grain size. The studies on cohesionless soils include those of Straub (1934), Laursen (1960Laursen ( , 1963, Komura (1966), Gill (1981), Lim (1998), Chang (1998), andSmith (1967).…”
Section: Attack Angle Effect On Maximum Shear Stressmentioning
confidence: 99%
“…In a very early paper, Straub [1] highlights how river contractions frequently occur when structures are built in restricting the river to achieve greater navigable flow depths. Lim [2] emphasizes how examples of river contractions are the gradual closing of a river prior to the construction of a dam or the partial constriction of a river either to build a spur dike into the flowing water or a cofferdam to enclose the work area for a structure from one side of the riverbank.…”
Section: Introductionmentioning
confidence: 99%